2021
DOI: 10.3390/aerospace8100305
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Design and Validation of Spaceborne High-Speed Digital Receiver Unit for Synthetic Aperture Radar Application

Abstract: This paper presents the effectiveness of the thermo-mechanical design of a high-speed digital receiver unit (HSDRU) developed for spaceborne synthetic aperture radar applications. The main features of HSDRU’s thermo-mechanical design include the thermal management of high-heat dissipation units by adopting heat sinks with the additional function of structural stiffeners and securing the heat rejection path to the upper side of electronics that interfaces the foil radiator for the on-orbit passive thermal contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Since these FPGAs are commercially available, implementation on FPGAs is much less expensive than implementation on application specific integrated circuits (ASICs). All the EEE-parts and materials used in DRX are space qualified, and through a space qualification test campaign, it is confirmed that all functions and performance of DRX are satisfied with the requirements under conditions considering the space environment [14]. In our SAR mode design, MDFT-BSF is used for highresolution modes; for the other modes such as standard modes and wide-swath modes, the decimation filter is used and MDFT-BSF is bypassed.…”
Section: Hardware Implementationmentioning
confidence: 76%
See 1 more Smart Citation
“…Since these FPGAs are commercially available, implementation on FPGAs is much less expensive than implementation on application specific integrated circuits (ASICs). All the EEE-parts and materials used in DRX are space qualified, and through a space qualification test campaign, it is confirmed that all functions and performance of DRX are satisfied with the requirements under conditions considering the space environment [14]. In our SAR mode design, MDFT-BSF is used for highresolution modes; for the other modes such as standard modes and wide-swath modes, the decimation filter is used and MDFT-BSF is bypassed.…”
Section: Hardware Implementationmentioning
confidence: 76%
“…In addition, we developed a spaceborne SAR digital receiver to show that MDFT-BSF can be implemented and operated on commercial spacegrade FPGAs. We used space-qualified EEE-parts and materials to manufacture the SAR digital receiver and completed the space qualification test campaign to confirm that it satisfies the function and performance requirements in space environment conditions [14].…”
Section: Introductionmentioning
confidence: 99%